PROFESIONALISME POLISI DALAM PENEGAKAN HUKUM - Raharjo, Agus; Angkasa, Angkasa (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Violence is often done by police in the investigation to get a confession the suspect. This behavior has become a habit that can be referenced from various research results, which are caused by lack of supervisory agency investigation, an incomplete legal instruments, the protection of the institution, and the unprofessional attitude of the police. This situation causes no chance to fight for a suspect his rights and the perpetrators of violence inaccessible. Professionalism associated with standardized moral issues into the code of conduct, and any violation of ethics code indicates a problem in the body of moral police. There should be a moral improvement in the investigator for investigation can take place properly and correctly according to expectations. Key words: police violence, investigation, criminal justice system, code of conduct